PERAN KEPERCAYAAN DALAM MEMEDIASI PERSEPSI NILAI TERHADAP NIAT BELI PRODUK RAMAH LINGKUNGAN - Sari Wulandari, Ni Luh Putu; Ekawati, Ni Wayan (E-Jurnal Manajemen, 2015)
ABSTRACT Trust associated with a sense of confidence that one has of a product, so that when the product is in accordance with what is promised, it will affect someone's purchase intention. Associated with it, trust can also arise through consumer perception of value is done by evaluating a product, so that the perception of value becomes important determinant in influencing customer trust and intention to buy the product. Determine the effect of perceived value on purchase intentions with confidence role as mediator is tujan of research. The study refers to the green marketing with eco-friendly products, namely Oriflame as research objects and locations in Denpasar research conducted with a sample of 105 respondents. The results of the analysis with path analysis and Sobel techniques prove the existence of a significant positive effect between the perception of value with the intention of purchasing the product, between perception and trust, and the trust with the intention of purchasing the product. Trust plays an important role and is able to mediate the perception of the value of the product purchase intention.
Keywords: trust, perceived value and purchase intention